2021
DOI: 10.1093/treephys/tpab155
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhizal-induced growth promotion and insect resistance reduction in Populus alba × P. berolinensis seedlings: a multi-omics study

Abstract: Arbuscular mycorrhizal (AM) fungi are an alternative to chemical insecticides or fertilizers, and there is an urgent need to extend the application of AM fungi to woody plants. This study aims to investigate the growth and resistance against the gypsy moth larvae (Lymantria dispar) in Glomus intraradices-colonized Populus alba × P. berolinensis seedlings, and to unravel the transcriptome and metabolome phenotypes recruited by AM fungus colonization that affect plant growth and insect resistance. Our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In some cases, this ecological speci city inhibits plant resistance and promotes the growth of harmful insects. In line with our previous studies, the present study revealed that GM and GI treatments respectively induced and decreased the resistance of P. alba × P. berolinensis seedlings to gypsy moth (Jiang et al 2021a;Jiang et al 2022). These results, together with the previous studies, demonstrated that speci c AMF colonization could induce alterations (either increase or decrease) in the plant resistance to insects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In some cases, this ecological speci city inhibits plant resistance and promotes the growth of harmful insects. In line with our previous studies, the present study revealed that GM and GI treatments respectively induced and decreased the resistance of P. alba × P. berolinensis seedlings to gypsy moth (Jiang et al 2021a;Jiang et al 2022). These results, together with the previous studies, demonstrated that speci c AMF colonization could induce alterations (either increase or decrease) in the plant resistance to insects.…”
Section: Discussionsupporting
confidence: 92%
“…The systematic investigation of AMF-induced plant resistance from the perspective of insects is still lacking. In our previous studies, we found that the inoculation with Glomus mossae (GM) improved the resistance to gypsy moth larvae in Populus alba × P. berolinensis seedlings, while inoculation with Glomus intraradices (GI) resulted in the opposite effect (Jiang et al 2021a;Jiang et al 2022). In the current study, leaves of P. alba × P. berolinensis inoculated with GM or GI were used to feed gypsy moth larvae, and the mechanism of mycorrhizal induced resistance/susceptibility was depicted at the microbial and metabolic level of gypsy moth larvae by combining the fat body metabolome and the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence to suggest that the differential effects of AMF on biotrophic versus necrotrophic pathogens are achieved via similar mechanisms. For instance, in poplars, mycorrhizal fungi regulate flavonoid biosynthesis (Jiang et al ., 2022) and can induce distinct responses in jasmonic acid and salicylic acid pathways (Jiang et al ., 2021). Second, in the meta‐analysis, fewer publications were found for biotrophic pathogens than for necrotrophic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, they show that transcripts associated with JA-dependent defenses and metabolites with insecticidal properties increased in leaves of gypsy moth-damaged, mycorrhizal poplar seedlings (Jiang et al 2021). Contrastingly, in a separate study, they found that gypsy moth-damaged, mycorrhizal poplar seedlings accumulated biomass but had reduced resistance to gypsy moth larvae (Jiang et al 2022). Taken together, these findings highlight the complexity of tripartite interactions.…”
Section: Introductionmentioning
confidence: 90%